Formulation of Instant Granules from Ethanolic Extract of Melinjo Peel (Gnetum gnemon L) Extract as Anti-Hyperuricemia - Sari, Diah Permata; Fahriati, Andriyani Rahmah; Maelaningsih, Firdha Senja (Jurnal Kefarmasian Indonesia, 2023)
Melinjo (Gnetum gnemon L) is extensively found in Indonesia, and all of its components are highly employed, with the fruit being the most commonly used. However, melinjo fruit can induce hyperuricemia if ingested excessively since it contains purines, which can raise uric acid levels. Several investigations have found that melinjo peel can lower uric acid levels in experimental rats in vivo. As a result, the goal of this study is to create and evaluate immediate granule formulations of melinjo peel extract. Plant determination, standardization of specified parameters, standardization of non-specific parameters, formulation, and physical and chemical assessment of instant granules of melinjo peel extract are all steps of the technique. This study employed two instant granule formulations of melinjo peel extract FI and FII with varying PVP concentrations (1g FI and 3g FII). Flow time testing, angle of repose testing, compressibility index testing, water content testing, and dissolving time testing were all part of the physical examination of instant granules. The chemical evaluation took the form of a UV-Vis spectrophotometer study of total flavonoid levels in instant extracts and granules. The FI and FII instant granule formulas had a yellow color, the flow time test results were in a good category (44 g/s and 81 g/s), the angle of repose test results was in the very good flow properties category (19° and 16°), the compressibility test results, the water content test, and the dissolving time test were performed in triplo, in 0, 7th, and 14th day, and the results were in a good category. In conclusion, the physical features of instant granules of FI and FII melinjo peel extracts fulfilled the requirements for all test parameters and had a high possibility to be produced as anti hyperuricemia preparations.